Technological Disaster Prevention: Technological Risks Assessment Process on High Technological Risk Supply Chain Activities - Choong, C. K.; Hamid, M.S.R.B.A.; Chew, B. C. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Technological risks approach silently and yet deadly. Once overlooked, technological disaster incident may occur- asset damage or even losses of human life. Negative impact of technological disaster may lead to organization supply chain toward disruption as organization facilities and labor force been impacted. Based on the circumstances, it is time to establish a technological risk assessment process to identify and assess technological risks along high technological supply chain activities. One of the largest petroleum organizations “Organization P” has been selected to investigate how the company assesses technological risks on supply chain activities and the technological risk factors that contain in each supply chain activities. A series of interview was conducted to collect respondent’s answer, while collected data were analyzed qualitatively. As conclusion, organization P obtained great achievement on technological disaster prevention as risk assessment process been enforces to assess risks on each supply chain activities. The technological risk assessment process contributes on preventing supply chain disruption while the identified technological risks demonstrated the high technological risk supply chain which contains double types of risks.